Hydroxyapatite pickering polyHIPEs and "thermo"HIPEs as injectable scaffolds for tissue engineering - Zhou,S; Bismarck,A; Steinke,JHG (Materials Research Society Symposium Proceedings, 2011)
Two types of porous materials derived from emulsion templates are described as potential scaffolds for tissue engineering. Novel oil-in-water particle stabilised, Pickering High Internal Phase Emulsions (HIPE) stabilised with hydroxyapatite (HAp) nanoparticles were prepared and polymerised to form stable polyHIPEs. By adding a water soluble glycidyl methacrylate (GMA) derivatised dextran as monomer to the continuous aqueous phase of the HIPEs, these Pickering-HIPEs stabilised by nontoxic biocompatible HAp nanoparticles, can be used as templates to manufacture interconnected high porosity macroporous hydrogels. A second type of emulsion templated "poly"HIPE was prepared without the need for covalent crosslinking chemistry which was replaced by a thermally-induced non-covalent scaffold forming process (thermoHIPE). These scaffolds form close to body temperature and potentially offer a new approach to the formation of injectable scaffolds for tissue engineering. © 2012 Materials Research Society.